Literature Review: Effectiveness of Canva Media in Science Learning on Students' Interests and Learning Outcomes - Syubhan Annur; Dodi Rizal Pradana; Fajrianour Qoyimah; Syifa Putri Mouthia; Muhammad Fuad Sya'ban (Journal of Science Education Research, 2026)
Canva is one of the many applications that teachers can use to create learning media. Canva simplifies the learning process for teachers and students by combining technology, skills, creativity, and other benefits. This is because Canva’s design features can enhance students' interest in learning activities, increase their motivation and learning outcomes by presenting instructional materials in an engaging way. The purpose of this study is to analyze the effectiveness of using Canva as a learning medium in increasing students' interest in learning and learning outcomes, and to find out how Canva can create interesting, interactive, and easy-to-understand learning. The data sources in this study are scientific articles published in national and international journals in the last 7 years (2017-2024) totaling 20 journal articles. Based on the analysis of the literature review of the 20 journal articles, it was found that Canva as an effective learning media in supporting distance learning. It was found that Canva as a learning medium is effective in supporting science learning activities in schools. Canva as a learning medium is considered effective for students in facilitating the understanding of abstract concepts in science subjects. The results of the study show that using Canva-based learning media can increase students' motivation and learning outcomes in science. Therefore, using Canva as an instructional medium is worth considering as a solution to improve the quality of education in schools.